The Linguistic And Content Knowledge Deficiencies Of EFL Learners’ Freewriting. UKMO Master Students (El-Wahat Journal for Research and Studies, 2025)
Among the major factors that could hinder EFL learners to acquire good freewriting writing are linguistic competence and the constant practice in writing innovatively (innovative writing). The study digs deep in what terms exactly and to what extent these reasons can be the major weaknesses in students’ writing. The aim behind this research is to help learner develop their writing competence. A questionnaire administered for a purposeful sample of 20 students of Master classes (linguistics, translation and literature) at Kasdi Merbah University Ouargla who are randomly selected for this study, with a test of freewriting given to just 2 students of the same sample. The results of this descriptive study show that EFL learners, though they reach an advanced stage of learning, they are still struggling with improving their syntactic, lexical and content knowledge of their writing. Keywords: EFL Learners, linguistic competence, freewriting, questionnaire, UKMO Learners